Effect of receiver shape and volume on the Alzheimer disease for molecular communication via diffusion. Issue 7 (1st September 2020) - Isik, Ibrahim; Yilmaz, H. Birkan; Demirkol, Ilker; Tagluk, Mehmet Emin
Abstract : Nano‐devices are featured to communicate via molecular interaction, the so‐called molecular communication (MC). In MC systems, the information is carried by molecules where the amount of molecules constitutes the level of the signal. In this study, an MC‐based system was analysed with different receiver topology and related parameters, such as size, shape, and orientation of receptors on the receiver. Also in the concept of nano‐medicine, the effect of amyloid‐beta ( A β ), which is believed as the main cause of Alzheimer disease, on the successful reception ratio of molecules with the proposed receiver models was investigated. It was demonstrated that the cubic receiver model is superior to sphere one in terms of the correct reception ratio of the molecular signal. A cubic model where its edge (not rotated around the centre) is placed across the transmitter demonstrated a better performance in reducing the effect of A β as compared to the sphere model while a cubic model where its corner (rotated around the centre) is placed across the transmitter demonstrated a worse performance than the spherical model. From this expression, it may be concluded that with the adjustment of topological system parameters the probability of successful reception ratio in MC may be possible.